How to Restart the Interventional Activity in the COVID‐19 Era: The Experience of a Private Pain Unit in Spain. Issue 8 (9th October 2020) - Abejón, David; Monzón, Eva M.; Deer, Tim; Hagedorn, Jonathan M.; Araujo, Ricardo; Abad, Cristina; Rios, Alberto; Zamora, Alejandro; Vallejo, Ricardo
Abstract: Introduction: The situation generated in the health system by the COVID‐19 pandemic has provoked a crisis involving the necessity to cancel non‐urgent and oncologic activity in the operating room and in day‐to‐day practice. As the situation continues, the need to reinstate attention for patients with chronic pain grows. The restoration of this activity has to begin with on‐site appointments and possible surgical procedures. On‐site clinical activity has to guarantee the safety of patients and health workers. Objectives: The objective of this review was to evaluate how to manage activity in pain units, considering the scenario generated by the pandemic and the implications of chronic pain on the immune system and proposed pharmacological and interventional therapies. Methods: Besides the established general recommendations (physical distance, surgical masks, gloves, etc.), we established specific recommendations that will allow patient treatment and relieve the disruption of the immune response. It is important to highlight the use of opioids with the least influence in the immune system. Further, individualized corticoid use, risk assessment, reduced immune suppression, and dose adjustment should take patient needs into account. In this scenario, we highlight the use of radiofrequency and neuromodulation therapies, techniques that do not interfere with the immune response. Conclusions: We describe procedures to implement these recommendations for individual clinical situations, the therapeutic possibilities and safety guidelines for each center, and government recommendations during the COVID‐19 pandemic.